A proof for the mode stability of a self-similar wave map. (4th July 2016) - Costin, O; Donninger, R; Xia, X
Abstract: We study the fundamental self-similar solution to the SU(2) sigma model, found by Shatah and Turok–Spergel. We give a rigorous proof for its mode stability. Based on earlier results by the second author, the present paper constitutes the last building block for a completely rigorous proof of the nonlinear stability of the Shatah–Turok–Spergel wave map.